Risk Factors of Hypoglycemia in Diabetics (Medical Forum Monthly, 2024)
Objective: To find the frequency ofrisk factorsof hypoglycemia in diabetics in our setup.Study Design: Prospective observational studyPlace and Duration of Study: This study was conducted at Emergency and Medical Wards Nishtar Hospital Multan from January 2010 to December 2013.Patients and Methods: One hundred and eighteen patients presented with hypoglycemia to Nishtar Hospital Multan. One hundred and eighteen diabetic patients above the age of 16 years admitted with hypoglycemia were included in the study. Written informed consent was taken from the patients or the attendants in case of patients with altered state of consciousness. Approval was taken from hospital ethical committee.Results: Mean age of patients was 60.46±14.20. Forty two patients (35.6%) were males and 76 (64.4%) were females. Mean duration of diabetes was 6.4±6.04years. Mean blood glucose level at the time of presentation was 36.25±12.49mg/dl. Thirty four (28.8%) patients had only neuroglycopenic symptoms without autonomic symptoms while 4(3.4%) hadautonomic symptoms alone. Eighty (67.8%) presented with both adrenergic and neuroglycopenic symptoms. Regarding risk factors, 77(65.25%) had renal failure, 66(55.93%) had missed meal, 37(31.35%) had vomiting, 23(19.49%) had recent increased dose of hypoglycemic agents, 19(16.10%) had delayed meal, 16(13.55%) had diarrhea, 14 (11.86%) had liver dysfunctionand 2(1.69%) had excessive physical activity.Conclusion: Hypoglycemia is common in old patients with long history of diabetes. Patients usually present late when they develop neuroglycopenic symptoms. Renal failure and missed meal are most common risk factors followed by vomiting and increased dosage of hypoglycemic agents. Patients need education about early symptoms of hypoglycemia, common risk factors and remedial steps to avoid this serious complication.